Perbandingan Pengadaan Persediaan Bahan Baku Dengan Menggunakan Metode EOQ dan Min Max pada PT XYZ - Mochamad Firgiawan Saripudin; Wahyudin (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
PT XYZ is an industrial company that produces vehicle spare parts. So far, raw material inventory planning has been carried out based on estimates of past needs, methods like this will result in uncertainty raw material needs which will cause total inventory costs to increase, stockouts, and overstocks. This research aims to evaluate the company's raw material inventory procurement, to obtain optimal raw material inventory procurement. The research methods used are normality tests, forecasting, and comparison of the EOQ & Min method where the best method is proposed to be applied in the company. The data collection techniques used were observation, interviews, and documentation. The research results show that companies should use the EOQ method for steel raw materials and Min Max for copper raw materials, which will save inventory costs by 25.16% or IDR 9,340,698. Apart from that, the safety stock value, maximum inventory, and reorder point are also known to avoid stockouts and overstocks. By implementing inventory procurement methods, companies can find out the maximum inventory that should be in the warehouse, expedite production operational activities, and save space usage which of course benefits the company.